HAART in treatment-experienced patients in the 21st century: the audacity of hope. (January 2009) - Conway, Brian
Evaluation of: Steigbigel RT, Cooper DA, Kumar PN et al. : Raltegravir with optimized background therapy for resistant HIV-1 infection. N. Engl. J. Med. 359, 339––354 (2008). Over the past decade the use of highly active antiretroviral therapy (HAART) has led to a significant increase in life expectancy, at least in drug-naive subjects. More recently, data generated in the BENCHMRK studies has extended this benefit to treatment-experienced patients, with over 60% of such individuals achieving maximal virologic suppression when treated with the integrase inhibitor raltegravir. If it is combined with darunavir and etravirine (as was done in the TRIO study), this benefit may be extended to over 90% of these patients. Similar results may also be achieved using maraviroc, an orally administered chemokine receptor antagonist. Unless new issues of long-term toxicity or drug resistance arise, we are now in a position to offer new hope to heavily treatment-experienced individuals living with HIV in a way that could not have been possible as recently as 2 or 3 years ago.